AYUDEEEEEEEEEEEEEENME EESS PARA HOY!!!!
![AYUDEEEEEEEEEEEEEENME EESS PARA HOY class=](https://us-static.z-dn.net/files/d27/8202d5162c56a72e98f96ddd52b97994.png)
![AYUDEEEEEEEEEEEEEENME EESS PARA HOY class=](https://us-static.z-dn.net/files/dd4/81ed873be5140431fcf490afb7b4b7fb.png)
Answer:
(x+3)(x-3) = x²-9
(a+4)(a-4) = a²-16
(2/3x²y+1/4)(2/3x²y-1/4) = ((4x^4)y²)/9-1/16
(2x²+3y³)(2x²-3y³) = 4x^4-9y^6
(b-2)(b-2)(b-2) = b³-6b²+12b-8
Step-by-step explanation:
(x+3)(x-3) = x²-9
(a+4)(a-4) = a²-16
(2/3x²y+1/4)(2/3x²y-1/4) = ((4x^4)y²)/9-1/16
(2x²+3y³)(2x²-3y³) = 4x^4-9y^6
(b-2)(b-2)(b-2) = b³-6b²+12b-8